2023
DOI: 10.1099/mgen.0.001010
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary tale of eight novel plasmids in a colistin-resistant environmental Acinetobacter baumannii isolate

Farzana T. Prity,
Liam A. Tobin,
Ram Maharajan
et al.

Abstract: Acinetobacter baumannii is an important opportunistic pathogen known for its high levels of resistance to many antibiotics, particularly those considered last resorts such as colistin and carbapenems. Plasmids of this organism are increasingly associated with the spread of clinically important antibiotic resistance genes. Although A. baumannii is a ubiquitous organism, to date, most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…These included 4 plasmids with the mcr-4.3 gene carried by strains recovered in clinical samples (two strains isolated in each of China and the Czech Republic) on an R3-T22 plasmid (Table S2). The remaining plasmid, p8E072658, was recently described in an environmental isolate from recycled fibre pulp in a paper mill in Finland 14 . This plasmid carries the novel mcr-4.7 colistin resistance gene in a Tn 3 -family transposon and encodes two novel R3-type Reps (R3-T73 and R3-T74).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These included 4 plasmids with the mcr-4.3 gene carried by strains recovered in clinical samples (two strains isolated in each of China and the Czech Republic) on an R3-T22 plasmid (Table S2). The remaining plasmid, p8E072658, was recently described in an environmental isolate from recycled fibre pulp in a paper mill in Finland 14 . This plasmid carries the novel mcr-4.7 colistin resistance gene in a Tn 3 -family transposon and encodes two novel R3-type Reps (R3-T73 and R3-T74).…”
Section: Resultsmentioning
confidence: 99%
“…However, the role of each plasmid type in dissemination of AMR genes remains to be established. To date, several studies have examined the role of A. baumannii plasmids in the spread of AMR genes 9,10,[14][15][16][17] but most of these studies have only reported on individual or a limited number of plasmids and thus, a comprehensive overview of how various plasmid types are involved in the dissemination of AMR genes remains elusive. In this study, we address this gap by examining the distribution of chromosomal sequence types, sampling, geographies, and AMR genes carried on plasmids originally included in the APT database alongside an additional 193 complete plasmids that have since been deposited in GenBank (as of August 18, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the results of Kirstahler, et al 19 who found that 53% of the circular DNA elements in their global sewage mobilome did not carry any identifiable MGE-related Pfam domains. However, several studies have identified small cryptic plasmids in bacterial isolates that contain no recognizable replication machinery [89][90][91][92] . It has been speculated that cryptic plasmids may play roles in viral defense 93 or functionally serving as empty backbones acquisition of novel genes 94 Additionally, some of these cryptic elements may represent currently undescribed classes of MGEs.…”
Section: Discussionmentioning
confidence: 99%